Emil's Clever Pig - Astrid Lindgren , Tony Ross
Whether he's teaching his pet pig to dance, being chased by a mad cow or wrestling a robber, Emil's adventures never stop. Hens, dogs, little sisters - and adults - all flee his path. But Emil doesn't mean to be bad, it's just that trouble - and fun - follow him wherever he goes. A collection of utterly engaging tales from one of the world's best-loved children's authors.